Rząd Donalda Tuska w 2024 roku. Realizacja obietnic wyborczych a rzeczywistość - Lekhchine, Omar (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This article examines the extent to which the campaign promises of Donald Tusk`s 2024 government have been fulfilled. Despite announcements of rapid reforms and the presentation of "100 concrete promises in 100 days", only 15 have been fully implemented. Key initiatives such as raising the tax-free threshold, legalising abortion up to the 12th week of pregnancy and abolishing the Church Fund faced numerous obstacles, including the lack of a stable parliamentary majority, internal coalition disputes and presidential vetoes. Although the government has embarked on judicial reforms and efforts to hold previous administrations accountable, the results of these actions remain limited. As a result, many promises have been postponed until after the 2025 presidential elections. The study, which used comparative and institutional methodologies, clearly identified a significant deficit in the effectiveness of the current government.
Keywords: Tusk, Donald (polityk polski; 1957- ); wybory; koalicja; obietnice wyborcze; 100 konkretów; skuteczność rządu; elections; coalition; electoral promises; 100 specific pledges; government effectiveness